Should companies pursue corporate social responsibility? - Onor, Nta Ojang (Department of Commercial Law, 2014)
There has been a long - standing argument on whether or not companies should be socially responsible. This is so because the primary objective of every company is to maximize profit for its shareholders, corporate social responsibility is therefore seen as a distraction. According to the leading proponent of this view Milton Friedman, 'the social responsibility of business is to increase its profits'i, but does society today stand to maximally benefit if the only concern of companies is to make a profit? Supporters of this view posit that companies involvement in projects not directly aimed at maximizing profit for its shareholders like corporate philanthropy and community development are unnecessary. They insist that issues like these should be left to the government and charities. On the contrary, society's present expectation of business covers a lot more than profit maximization; companies' involvement in corporate social responsibility is therefore the only way these expectations could be harnessed. Corporate social responsibility (CSR) is not only about philanthropy as some think, it involves the myriad ways firms integrate social, environmental and economic concerns into the day to day running of their companies. This essay stresses the need for companies' involvement in corporate social responsibility; it seeks to show that a socially responsible company does not only bring environmental and social benefits to the society at large, but also attracts financial benefits for the company involved. It goes further to suggest strategies that could be used to make companies more responsive to social needs than they presently are. The first chapter answers the question, what is corporate social responsibility? Many people and organizations have attempted defining this concept, but more often than not their views do not entirely reflect what corporate social responsibility is about because of the wide spectrum of issues it covers. To some people, corporate social responsibility is all about corporate philanthropy, to others it is more encompassing than that and is closely linked with principles of sustainable development. Although people look at CSR from different perspectives, what is generally agreed by all advocates of corporate social responsibility is that the management of companies should not only consider the interests of shareholders when running the company, but should take into account the welfare of other company stakeholders. Sustainable Development is defined by the United Nations Brundland Commission as 'development that meets the needs of the present without compromising the ability of future generations to meet their own needs'.ii The fact that CSR is voluntary leaves companies with discretion to be socially responsible or not. It is the voluntary nature of CSR that makes some people view CSR as basically corporate philanthropy. Those who see CSR as broader than philanthropy and linked with the principles of sustainable development argue that while philanthropy is absolutely discretionary,CSR is sustainable. While philanthropy involves how companies' profits are spent on deserving causes, CSR is concerned with how these profits are made in the first place. Proponents of CSR as an intrinsic part of sustainable development further argue that it is only when social accountability becomes an integral part of corporate conduct rather than a philanthropic add on, that the economic development of the private sector will move forward within an acceptable framework of public purposeiii This is my preferred notion of corporate social responsibility. Chapter one outlines the various definitions of corporate social responsibility. It looks at the relationship between corporate social responsibility and corporate governance and also gives an overview of the background influences of CSR. Chapter two examines the criticisms of corporate social responsibility and counters them. Chapter three presents the business case for corporate social responsibility; it seeks to show that socially responsible companies are not disadvantaged but enjoy numerous financial benefits. Chapter four suggests strategies that could be used to make companies more responsive to societal needs. Flowing from the fact that CSR is voluntary and some companies remain unresponsive to societal needs, regulation of aspects of CSR that cannot be left at the mercy of companies remains a way socially irresponsible companies would be compelled to comply. This chapter presents the arguments for and against legislation of CSR and suggests a balanced regulatory approach to corporate social responsibility.